ANALISIS DAYA DUKUNG LAHAN PERTANIAN SAWAH DI KECAMATAN PULAU PUNJUNG KABUPATEN DHARMASRAYA - Fitra.R, Muhammad Afif; Umar, Iswandi (JURNAL BUANA, 2026)
Pulau Punjung Subdistrict continues to experience an increase in development and the quality of the population is quite rapid. This can lead to a reduction in the area of agricultural land and a decrease in food production. This research aims to (1) Knowing the level of carrying capacity of paddy fields, (2) Knowing the population projection in 2035 (3) Knowing the need for food and agricultural land in 2035. The method used is descriptive quantitative method. The analysis technique uses a mathematical formula theory of Odum et all.,in Soeharjo and Tukiran (1990). The results of the study show that the level of carrying capacity of lowland agricultural land in 2010-2020 has an optimal land carrying capacity. The results of the KLPR calculation, the need for agricultural land for rice fields in Pulau Punjung District for 2035 has been fulfilled from the available rice fields in 2035. The calculation of rice production for 2035 has increased, so that rice consumption needs can be met.